Korelasi Unsur Antara U dengan Co, Ni, Ag, Mo pada Batuan Granit dan Kuarsit di Jumbang I, Kalimantan Barat - Sularto, Priyo (EKSPLORIUM, 2012)
Jumbang I sector is a part of the basin Kalan, West Kalimantan. As the other areas in Kalan, Jumbang I also have geochemical anomalies of uranium element in Vein of quartzite rocks at several locations, with high grade and radioactivities value between 500 c/s - 15000 c/s. Besides of the uranium element there are other elements included Co, Ni, Ag and Mo. The analysis result of 49 rock samples using Fluorimeter Jarell Ash obtained grades of U: 13 ppm - 31000 ppm and by Atomic Absorption Spectrometer obtained grades of Co : 1.5 ppm - 83.5 ppm, Ni : 15.2 ppm - 507.6 ppm, Ag: 1.2 ppm - 10.8 and Mo: 31.7 ppm - 10 738 ppm. To determine of element relationship in these rocks is using correlation method. The aim of this study is to determine of the relationship between U and Co, Ni, Ag, Mo elements. The methods of this study are statistical regression and correlation. The results of this study are obtained the correlation coefficient (R) between U – Co = 0.23, U - Ni = 12.15, U - Ag = 0.50, U - Mo = 0.86. Correlation coefficient (R) 0.86 can be interpreted as a high correlation, it means that the U element has strong associate with Mo element and weak associate with Co, Ni, Ag elements.